1998
DOI: 10.1111/j.1469-7793.1998.341bw.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of a swelling‐activated chloride current in bovine endothelium by protein tyrosine phosphorylation and G proteins

Abstract: The role of protein tyrosine phosphorylation and of G proteins in the activation of a swelling‐activated Cl− current (ICl,swell) in calf pulmonary artery endothelial (CPAE) cells was studied using the whole‐cell patch clamp technique. ICl,swell was activated by reducing the extracellular osmolality by either 12.5 % (mild hypotonicity) or 25 % (strong hypotonicity). The protein tyrosine kinase (PTK) inhibitors tyrphostin B46, tyrphostin A25 and genistein inhibited ICl,swell with IC50 values of, respectively, 9.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
144
3

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 154 publications
(155 citation statements)
references
References 32 publications
8
144
3
Order By: Relevance
“…This activation is transient and occurs without any change in cell volume. Moreover, activation of ICl,swell is significantly impaired in the presence of intracellular GDPâS (Doroshenko & Neher, 1992;Voets et al 1998). However, these effects of GTPãS and GDPâS did not give any clue to the kind of G proteins that are involved.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This activation is transient and occurs without any change in cell volume. Moreover, activation of ICl,swell is significantly impaired in the presence of intracellular GDPâS (Doroshenko & Neher, 1992;Voets et al 1998). However, these effects of GTPãS and GDPâS did not give any clue to the kind of G proteins that are involved.…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular application of GTPãS has been shown to activate ICl,swell in several cell types (e.g. Doroshenko et al 1991;Tilly, 1991;Nilius et al 1994;Mitchell et al 1997;Voets et al 1998). This activation is transient and occurs without any change in cell volume.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A direct effect of ⌫ i on VRAC seems unlikely, as activation of the current by lowered ⌫ i remains dependent on protein tyrosine kinase activity (6,30). We favor the idea that ⌫ i acts similar to a second messenger, and directly or indirectly regulates the activity of the intracellular enzyme(s) that mediate the activation of I Cl,swell .…”
mentioning
confidence: 88%
“…20,28 In addition, signaling pathways contributing to VRAC activity include phosphatidyl-inositol-3-phosphate kinase (PI3K), NADH-dependent oxidases and reactive oxygen species (ROS) as well as tyrosine kinases. [29][30][31][32][33][34][35][36] Recently it was demonstrated that knockdown of integrin b 1 reduces RVD in adherent Ehrlich Lettre ascites cells (ELA) cells 37 and as integrin b 1 stretch in Figure 1. VRAC characteristics.…”
Section: Biophysical Characterization Of Vracmentioning
confidence: 99%